2015
DOI: 10.3746/jkfn.2015.44.10.1504
|View full text |Cite
|
Sign up to set email alerts
|

Development and Validation of Analytical Method for Pectolinarin and Pectolinarigenin in Fermented Cirsium setidens Nakai by Bioconversion

Abstract: The aim of this study was to investigate a validation method for determination of pectolinarin and pectolinarigenin in fermented Cirsium setidens Nakai. For validation, the specificity, linearity, precision, accuracy, detection limits, and quantification limits of pectolinarin and pectolinarigenin were measured by HPLC. The results show that the detection limits of pectolinarin and pectolinarigenin were 4.25 μg/mL and 2.46 μg/mL, respectively. The recovery rates of pectolinarin and pectolinarigenin were high i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 22 publications
0
7
0
Order By: Relevance
“…Food consumption for the previous year was assessed with a food frequency questionnaire (FFQ), which included 114 food items and has been validated elsewhere 23. Dietary intakes of nutrients and food groups were analyzed using CAN-pro 3.0 software (The Korean Nutrition Society, Seoul, Korea).…”
Section: Methodsmentioning
confidence: 99%
“…Food consumption for the previous year was assessed with a food frequency questionnaire (FFQ), which included 114 food items and has been validated elsewhere 23. Dietary intakes of nutrients and food groups were analyzed using CAN-pro 3.0 software (The Korean Nutrition Society, Seoul, Korea).…”
Section: Methodsmentioning
confidence: 99%
“…Besides the effects Cirsium setidens Nakai has on anti-oxidant, anti-inflammation, anti-cancer, and anti-adipogenesis [18,21,22,23], it has been supported that Cirsium setidens Nakai contains potential as a natural edible plant against obesity. Moreover through this study, we showed that the fermentation improved the quantity of bioactive compound in Cirsium setidens Nakai [24], which might stimulate the protective mechanisms against abnormalities in obesity. However, the detailed mechanism of how…”
Section: Introductionmentioning
confidence: 65%
“…Extracts were filtered and evaporated under vacuum, dried at -70°C. FCSN was standardized by HPLC (Waters 2695, Waters Co., Milford, MA, USA) [24].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…This questionnaire has been validated previously and also includes questions about whether the child has eaten 113 food items during the preceding year. The amount of each food item that was eaten is measured by using nine non-overlapping intake frequencies (ranging from “rarely eaten” to “eaten more than three times per day”) together with three portion sizes (small, average, and large) [35]. The food and dietary intake is assessed by using a computerized nutrient-intake assessment software program (CAN-Pro 3.0; Korean Nutrition Society, Seoul, Korea) [36].…”
Section: Methodsmentioning
confidence: 99%